2017
DOI: 10.3892/mmr.2017.6529
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modifications and their applications in eye research

Abstract: Abstract. Gene expression is the process by which genetic information is used for the synthesis of a functional gene product, and ultimately regulates cell function. The increase of biological complexity from genome to proteome is vast, and the post-translational modification (PTM) of proteins contribute to this complexity. The study of protein expression and PTMs has attracted attention in the post-genomic era. Due to the limited capability of conventional biochemical techniques in the past, large-scale PTM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 190 publications
(126 reference statements)
0
10
0
1
Order By: Relevance
“…Post-translational modification, which occurs by adding modifying molecules to amino acids or removing or altering these modified amino acids, is important for proper folding, transport/trafficking, localization, function, regulation, and/or degradation of proteins. Examples of post-translational modifications include phosphorylation, glycosylation, acetylation, ubiquitination, sumoylation, methylation, and lipidation [416]. Kinases that affect activity by mediating phosphorylation states are described elsewhere, however, post-translational modification genes affecting glycosylation and lipidation/prenylation are prominent among those that lead to PR degeneration.…”
Section: Category 10: Dna Repair Rna Biogenesis and Protein Modificmentioning
confidence: 99%
“…Post-translational modification, which occurs by adding modifying molecules to amino acids or removing or altering these modified amino acids, is important for proper folding, transport/trafficking, localization, function, regulation, and/or degradation of proteins. Examples of post-translational modifications include phosphorylation, glycosylation, acetylation, ubiquitination, sumoylation, methylation, and lipidation [416]. Kinases that affect activity by mediating phosphorylation states are described elsewhere, however, post-translational modification genes affecting glycosylation and lipidation/prenylation are prominent among those that lead to PR degeneration.…”
Section: Category 10: Dna Repair Rna Biogenesis and Protein Modificmentioning
confidence: 99%
“…Ubiquitination is a post-translational modifications of proteins that plays an important role in regulating the structure and function of proteins. 42 The current study found the core genes of PPI network constructed by target genes of DE-miRs to be related to ubiquitination; thus, further investigation of the specific proteins involved in ubiquitination and the interaction of these proteins may open up new perspectives in myopia research and drug targets. [43][44][45] There are a few limitations in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…The lens protein conversion rate is negligible, and therefore accumulates PTM throughout the aging process. PTMs such as carbamylation, phosphorylation, methylation, deamidation, advanced glycosylation, and oxidative modification, have been identified in human lens proteins in aging and cataracts [91][92][93].…”
Section: Others: Lens Proteinmentioning
confidence: 99%